Children’s Literature in Canadian Commercial Reading Programs - Phillips, Linda; Leithead, Marion; Smith, Martha (Canadian Journal of Education/Revue canadienne de l'éducation, 2002)
In this study we analyzed the use of children’s literature in three widely used commercially published and literature-based reading programs for grades 1 to 6. On average, 37% of the literature selections had been previously published, with a range by publisher of 4% to 55%. These percentages are noticeably lower than those reported for American programs published about the same time. The publishers changed the selections from their original trade book publication in two key areas: text content and illustrations. The changes frequently altered the intent, content, and meaning of the selections, and in some cases rendered the stories incomprehensible. Keywords: children’s literature, commercial reading programs, trade books, illustrations L’article porte sur l’analyse de l’usage fait de la littérature de jeunesse, généralement utilisée et publiée sur une base commerciale, dans trois programmes de lecture fondés sur la littérature, pour les enfants de la 1ère à la 6e année. En moyenne, 37 % de la littérature sélectionnée avait été publiée antérieurement, au taux de 4 à 55 % par éditeur. Ces pourcentages sont beaucoup plus bas que ceux rapportés pour les programmes américains publiés dans la même période. Les éditeurs ont changé les sélections de la publication de nature commerciale initiale dans deux domaines à deux niveaux : le contenu textuel et les illustrations. Les changements apportés modifient fréquemment la finalité, le contenu et le sens des sélections, et rendent dans certains cas l’histoire incompréhensible. Mots-clés : littérature de jeunesse, programmes de sensibilisation critique à la lecture de contenus publicitaires, publication commerciale, illustrations